Qur’anic Insights on Structural Femicide Reflected in Bida’ah - Ulfa, Aria; Hidayati, Sifani; Sadali, Achmad Dafid Imron (Indonesian Journal of Islamic Studies, 2025)
General Background: Structural femicide persists globally as a form of gender-based violence embedded within patriarchal sociocultural and religious systems. Specific Background: In Muslim-majority societies, distorted interpretations of Qur’anic teachings often legitimize violence against women, a dynamic vividly portrayed in the Malaysian series Bida’ah. Knowledge Gap: Existing studies rarely integrate Qur’anic thematic exegesis with media analysis to reveal how religious narratives are misused to reinforce systemic oppression. Aims: This study investigates the conceptual foundations of structural femicide, analyzes its narrative representation in Bida’ah, and reinterprets Qur’anic verses emphasizing justice and the sanctity of life. Results: Findings indicate that Bida’ah reflects multilayered violence—physical, symbolic, and institutional—sustained through patriarchal power and manipulated religious authority. The Qur’an, however, does not justify such violence; rather, it promotes protection, equality, and moral justice. Novelty: The study offers an integrated framework combining thematic Qur’anic interpretation and social hermeneutics with cinematic analysis to expose the ideological mechanisms underlying structural femicide. Implications: These insights highlight the urgency of contextual, justice-centered Qur’anic interpretation to dismantle patriarchal norms and to strengthen discourses countering gender-based violence. Highlights: Shows how distorted Qur’anic interpretations legitimize structural violence against women. Uses the Bida’ah series to illustrate multilayered femicide: physical, symbolic, and institutional. Emphasizes contextual, justice-oriented exegesis to dismantle patriarchal religious narratives. Keywords: Structural Femicide, Qur’anic Interpretation, Gender Based Violence, Patriarchal Power, Bida’ah Series